Policy Transfer and Social Stratification: Park Chung-hee’s Middle-Class Socialization in South Korea and Implications for Vietnam - Thu, Phan Thi Anh; Dang, Vo Pham Khanh (Journal of Social Science and Humanities, 2025)
In the context of industrialization and modernization of the country, the Park Chung-hee administration (1961-1979) proactively sought solutions for sustainable national development. Accordingly, the middle-class socialization policy in the Republic of Korea (ROK) is identified as one of the important solutions to promote this class to contribute to national prosperity, helping the ROK become a modern industrial country, and moving from authoritarian politics to a democratic society. Based on that reality, the research analyzes and explains the middle-class socialization policy in the ROK under President Park Chung-hee, starting from the formation basis, characteristics, and policy results. At the same time, from the experience of the ROK, the article proposes some suggestions as a reference for Vietnam in building and developing a harmonious, dynamic, and sustainable society.